385. OUTCOME FOLLOWING MINIMAL INVASIVE VERSUS OPEN ESOPHAGECTOMY FOR ESOPHAGEAL CARCINOMA PATIENTS WITH LIVER CIRRHOSIS: A PROPENSITY SCORE-MATCHED ANALYSIS. (24th September 2022) - Lin, Yi-yu; Chiu, Chien-Hung; Tsai, Chun-Yi; Chao, Yin-Kai
Abstract: Although minimally invasive esophagectomy (MIE) has advanced into a safe and effective alternative to open esophagectomy (OE), its utility in cirrhotic esophageal cancer (EC) patients remained unknown. This study analyzed the perioperative outcomes of MIE for EC with LC compared with open esophagectomy (OE). We retrospectively reviewed the clinical charts of patients treated with esophagectomy for EC who had a concomitant diagnosis of LC. Of the 74 patients identified from our records, 43 underwent MIE and 31 OE. The two treatment groups underwent propensity scores (PS) matching using a logistic model that included the following covariates: type of preoperative therapy, Charlson comorbidity index, Child-Pugh class, and elective versus emergency surgery. Following PS matching, the MIE and OE groups consisted of 40 and 20 patients, respectively. Patients treated with MIE less frequently showed severe pneumonia (7.5% versus 30%, respectively, p = 0.049) and had a shorter length of stay (median: 16 versus 22 days, respectively, p = 0.009), albeit at the expense of a longer operating time (median: 465.5 versus 403 min, respectively, p = 0.015). Compared with OE, MIE was associated with a lower in-hospital mortality (25% versus 2.5%, respectively, p = 0.013). Moreover, MIE did not compromise the quality of resected specimens with similar R0 resection rate. EC patients with LC showed more favorable mortality figures and lower rates of severe pneumonia after MIE compared with those who underwent OE. MIE may serve as a safe and feasible alternative for selected EC patients with LC.